C950T and C1181G osteoprotegerin gene polymorphisms in myeloma bone disease. Issue 4 (June 2014) - Sonmez, Mehmet; Kazaz, Nazlı; Yucel, Burcu; Topbas, Murat; Ucar, Fahri
<x content-type="archive" xml:space="preserve">Abstract</x> Objectives Bone disease is one of the hallmarks of multiple myeloma (MM). The role of osteoprotegerin (OPG) in the RANK/RANKL/OPG signaling system is well defined in the myeloma bone disease. Polymorphisms of the TNFRSF11B gene encoding OPG have been studied in various bone diseases. However, relationship between the levels of OPG and development of bone lesions regardless of RANKL is yet unknown. In this study, the effects of OPG gene polymorphism on the development of bone lesions in MM were investigated. Methods C950T and C1181G polymorphisms of the OPG gene were studied in 52 MM patients (36 with bone lesions and 16 without bone lesions) and in another 20 control subjects using DNA sequencing. Results 1181 G and 950 T alleles were overrepresented in MM patients having bone lesions. 950 TT/1181 GG haplotype frequency and TT/GG combined haplotype were also higher in MM patients having bone lesions compared to MM patients without bone lesions or to control. Discussion This is the first study searching for the relationship between OPG gene variants C950T (promoter), C1181G (exon 1), and myeloma bone disease. It was concluded that the presence of polymorphic 1181 G/950 T alleles and 950 TT/1181 GG genotypes may play a role in the development of bone disease.